2018
DOI: 10.1071/an16576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forage type and age at which forage provision is started on growth performance, rumen fermentation, blood metabolites and intestinal enzymes in Holstein calves

Abstract: The aim of this study was to determine the effects of two forage sources supplemented either from Day 3 or Day 15 of age on growth performance, rumen fermentation, blood metabolites, intestinal enzymes and incidence of diarrhoea in Holstein bull calves. Forty neonatal male Holstein calves (40.6 ± 5.8 kg BW) were randomly assigned to five treatments, with eight replicates each, including calves fed starter feed without any forage provision (Control; CON), and the same starter plus either chopped alfalfa hay sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Both studies observed improved DMI and growth performance with forage provision, and the greatest growth performance and rumen development were obtained in calves offered hay from the 2nd week rather than the 4th or 6th week of age [75,76]. Based on these studies, suggestions may be made to include alfalfa or oat hay in diets of calves as early as week 2 or even right after birth in order to improve DMI and ADG in dairy calves [24,75].…”
Section: Forage Physical Forms and Processingmentioning
confidence: 92%
See 3 more Smart Citations
“…Both studies observed improved DMI and growth performance with forage provision, and the greatest growth performance and rumen development were obtained in calves offered hay from the 2nd week rather than the 4th or 6th week of age [75,76]. Based on these studies, suggestions may be made to include alfalfa or oat hay in diets of calves as early as week 2 or even right after birth in order to improve DMI and ADG in dairy calves [24,75].…”
Section: Forage Physical Forms and Processingmentioning
confidence: 92%
“…A summary of studies related to forage particle size and methods of processing forage in pre-weaned dairy calves. Time [24,75,76] and method [25,77,78] of offering forage are essential factors that can influence how dairy calves utilize forage. While Wu et al [24] found no differences in DMI, ADG, and rumen development in calves fed alfalfa hay or oat hay either at day 3 or 15 of age, different outcomes were shown in two other studies, investigating the effect of age at which alfalfa hay [75] and oat hay [76] were introduced to calves.…”
Section: Forage Physical Forms and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Calves with hay supplementation initiated at two weeks of age showed the best productivity. Another study found that feeding forage to calves, either from 3 or 15 days of age, had no effect on growth rate, feed intake and rumen fermentation parameters compared to calves fed no forage, which also justified the supply of forage to young calves [60]. Inclusion of forage in the starter feed was positively linked with muscular development of the rumen [61,62] and morphological appearances of rumen epithelial cells, and caused decreased plaque formation [40,61].…”
Section: Strategies To Promote Rumen Developmentmentioning
confidence: 99%